THE STUDENTS' READING ANXIETY AND READING STRATEGIES IN EFL LEARNING - Eva Meidi Kulsum, - (2018)
Numerous students experience anxiety in reading, particularly, when they are asked to read a foreign language text. There are some factors that must be taken into account such as the cultural background of the text, the ability of the language being read, the unfamiliarity of the scripts, and the writing systems of the text. This study examined the sources of students' reading anxiety and the use of reading strategies to overcome the anxiety in EFL reading. It employed a qualitative descriptive method and was considered as a case study design. EFLRAI adopted from MasoudZoghi (2012), RSQ adopted from Oxford et al. (2004), and a semi-structured interview were used as the instrumentations and materials in this study. The data from EFLRAI and RSQ were analyzed qualitatively by calculating manually the percentages and mean scores of the student responses to infer the data findings. The interview data were analyzed to corroborate and confirm the data from questionnaires. The result of this study showed that most of the students considered top-down reading anxiety as the most affecting source causing anxiety in EFL reading (35.78%). It was followed by the bottom-up reading anxiety (34.86%) and classrooms reading anxiety (29.36%). On the other hands, students preferred to use top-down reading strategies (55.38%) rather than bottom-up reading strategies (44.62%). In addition, the students' reading anxiety is mostly derived from the text. Therefore, choosing an appropriate text is important in order to decrease the students' reading anxiety and increase their interest and comprehension in reading. Besides, it is also inferred that the effectiveness of the use of a certain strategy does not depend on the strategy itself, what makes a strategy effective is associated with how it is employed. Therefore, teaching on how to use reading strategies is useful to improve students' comprehension since effective strategies can be taught and reading comprehension can be improved through instruction.--------Banyak siswa mengalami kecemasan saat membaca, terutama ketika mereka harus membaca teks bahasa asing. Ada beberapa faktor yang harus diperhatikan seperti latar belakang budaya teks, kemampuan bahasa dibaca, skrip yang tidak dikenal, dan sistem penulisan teks. Penelitian ini meneliti sumber kecemasan membaca siswa dan penggunaan strategi membaca untuk mengatasi kecemasan dalam membaca teks Bahasa Inggris. Penelitian ini menggunakan metode deskriptif kualitatif dan dianggap sebagai desain studi kasus. EFLRAI diadopsi dari MasoudZoghi (2012), RSQ diadopsi dari Oxford et al. (2004), dan wawancara semi terstruktur digunakan sebagai instrumentasi dan materi dalam penelitian ini. Data dari EFLRAI dan RSQ dianalisis secara kualitatif dengan menghitung secara manual persentase dan skor rata-rata tanggapan siswa untuk menyimpulkan temuan data. Data wawancara dianalisis untuk menguatkan dan mengkonfirmasi data dari kuesioner. Hasil penelitian ini menunjukkan bahwa sebagian besar siswa menganggap kecemasan membaca top-down sebagai sumber yang paling mempengaruhi kecemasan dalam membaca EFL (35,78%). Hal ini diikuti oleh kecemasan membaca bottom-up (34,86%) dan kecemasan membaca classroom (29,36%). Di sisi lain, siswa lebih suka menggunakan strategi membaca top-down (55,38%) daripada strategi membaca bottom-up (44,62%). Selain itu, kecemasan membaca siswa sebagian besar berasal dari teks. Oleh karena itu, memilih teks yang tepat penting guna mengurangi kecemasan membaca siswa dan meningkatkan minat dan pemahaman mereka dalam membaca. Selain itu, disimpulkan juga bahwa keefektifan penggunaan strategi membaca tidak bergantung pada strategi itu sendiri, yang membuat strategi efektif adalah terkait dengan bagaimana penerapannya. Oleh karena itu, pengajaran tentang bagaimana menggunakan strategi membaca yang baik sangat dianjurkan untuk meningkatkan pemahaman siswa karena strategi yang efektif dapat diajarkan dan pemahaman bacaan dapat ditingkatkan melalui pengajaran.